Chronic Venous Disorders: A Contemporary Review (Cardiovascular Journal, 2019)
Chronic venous disease is a common medical condition of the lower limbs that affects a large number of people in every part of the world including the Indian subcontinent. The disease is insidious in nature and therefore often ignored in the early stages. In advanced stages, it causes significant discomfort in the affected limbs which adversely influences quality of life, work hours and treatment expenses. The present article reviews the various aspects of the disease including its pathophysiology and recent management updates.Cardiovasc. j. 2019; 12(1): 59-63